Selected Decisions (2nd Ed). (Selected Decisions; Issue, Year, 1963)
This paper analyses several IMF's selected decisions of the Executive Board and selected documents. Each member shall furnish to the IMF the data necessary to determine its net official holdings of gold and United States dollars. The usability of gold or dollars for the payment of the gold subscription is not necessary to constitute 'holdings.' It has been decided to recommend to the Board of Governors, where a member presents, for reasons which it shall submit to the IMF, that its reserves should not be reduced by an immediate 25 percent gold payment, that such member shall be permitted in accordance with an appropriate resolution to have its quota increased in five annual installments, with the right to accelerate the payment of such installments. In June 1947, the IMF issued a statement recommending to its members that they take effective action to prevent external transactions in gold at premium prices, because such transactions tend to undermine exchange stability and to impair monetary reserves.